Aerial mapping of Seri Menanti, Negeri Sembilan - Abdullah, Alias; Ibrahim, Illyani; Ibrahim, Mansor; Hj. Mohd. Noor, Norzailawati; Harun, Nor Zalina; Abdul Latip, Nurul Syala; Abdullah, Ahmad Afiq Aiman; N Murtaza, Fatin Farhana
Drone aerial image of 1 km radius from Istana Lama Seri Menanti, Negeri Sembilan